284 CARBAPENEM-RESISTANT STRAIN OF KLEBSIELLA PNEUMONIAE HARBORING ONE COPY OF THE SERINE CARBAPENEMASE KPC-2 AND TWO COPIES OF A TEM-TYPE EXTENDED-SPECTRUM β-LACTAMASE GENE. Issue 1 (1st January 2007) - Tulloch, L.; Qin, X.; Rutledge, J.
Abstract : Background: Strains of Klebsiella pneumoniae with multiple determinants of drug resistance present a serious management problem. The determinants that confer resistance to cephalosporins and carbapenems are of particular interest since these drugs are frequently used in the treatment of Enterobacteriaceae infections. Extended-spectrum β-lactamases (ESBLs), in general, hydrolyze third-generation cephalosporins and aztreonam (a monobactam). The TEM, SHV, and CTX-M families are the most prominent ESBLs. Carbapenem-hydrolyzing β-lactamases (carbapenemases) hydrolyze the substrates of ESBLs and the carbapenems; ertapenem, imipenem, and meropenem. Two types of carbapenemases can be described: serine carbapenemases, which possess a serine moiety and can be inhibited by β-lactamase inhibitors (ie, clavulanate and tazobactam) and metallo-β-lactamases (MBLs), which require divalent cations, usually zinc, for enzyme activity and thus can be inhibited by EDTA and similar divalent cation chelators. The most prominent serine carbapenemases are those of the KPC (group A), Amp-C (group C), and OXA (group D) families and the most prominent MBLs belong to the IMP, VIM, and SPM families (group B). Study Design and Methods: Using a combination of susceptibility testing, PCR targeting, and DNA sequencing, we characterized the phenotype and genotype of a carbapenem-resistant strain of K. pneumoniae (KpM) recovered from a pediatric patient in Seattle, Washington. Results: KPC and TEM and the integron-related structures Int1, Int3, and Sul3 were amplified from KpM. Transformation of laboratory strains of Escherichia coli with KpM plasmid DNA yielded two daughter strains: KpM(KPC), which displays the carbapenemase phenotype, and KpM(TEM), which demonstrates the ESBL phenotype. KPC-2 and a TEM-type gene were amplified from KpM(KPC) and a TEM-type gene and Int3 were amplified from KpM(TEM). Conclusion: These results (1) classified the genes responsible for the resistance pattern of KpM and (2) demonstrated that the resistance determinants were plasmid- and possibly integron-borne.